Assessment of patient-reported outcome measures in pleural interventions. Issue 1 (3rd July 2017) - Psallidas, Ioannis; Yousuf, Ahmed; Talwar, Ambika; Hallifax, Rob J; Mishra, Eleanor K; Corcoran, John P; Ali, Nabeel; Rahman, Najib M
Abstract : Introduction: There is a lack of data evaluating the clinical effect on symptoms of pleural intervention procedures. This has led to the development of patient-reported outcome measures (PROMs) to define what constitutes patient benefit. The primary aim of this paper was to prospectively assess the effect of pleural procedures on PROMs and investigate the relationship between symptom change and clinical factors. Methods: We prospectively collected data as part of routine clinical care from 158 patients with pleural effusion requiring interventions. Specific questionnaires included two patient-reported scores (a seven-point Likert scale and a 100 mm visual analogue scale (VAS) to assess symptoms). Results: Excluding diagnostic aspiration, the majority of patients (108/126, 85.7%) experienced symptomatic benefit from fluid drainage (mean VAS improvement 42.6 mm, SD 24.7, 95% CI 37.9 to 47.3). There was a correlation between symptomatic benefit and volume of fluid removed post aspiration. A negative association was identified between the number of septations seen on ultrasound and improvement in dyspnoea VAS score in patients treated with intercostal chest drain. Conclusion: The results of our study highlight the effect of pleural interventions from a patient's perspective. The outcomes defined have the potential to form the basis of a clinical useful tool to appraise the effect, compare the efficiency and identify the importance of pleural interventions to the patients.